Prevalence of myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) in Australian primary care patients: only part of the story? - Nneka Orji; Julie A. Campbell; Karen Wills; Martin Hensher; Andrew J. Palmer; Melissa Rogerson; Ryan Kelly; Barbara de Graaff (BMC, 2022)
Abstract Background ME/CFS is a disorder characterized by recurrent fatigue and intolerance to exertion which manifests as profound post-exertional malaise. Prevalence studies internationally have reported highly variable results due to the 20 + diagnostic criteria. For Australia, the prevalence of ME/CFS based on current case definitions is unknown. Objectives To report prevalence of ME/CFS in patients aged ≥ 13 years attending Australian primary care settings for years 2015-2019, and provide context for patterns of primary care attendance by people living with ME/CFS. Methodology Conducted in partnership with the Patient Advisory Group, this study adopted a mixed methods approach. De-identified primary care data from the national MedicineInsight program were analyzed. The cohort were regularly attending patients, i.e. 3 visits in the preceding 2 years. Crude prevalence rates were calculated for years 2015-2019, by sex, 10-year age groups, remoteness and socioeconomic status. Rates are presented per 100,000population (95% confidence intervals (CI)). Qualitative data was collected through focus groups and in-depth 1:1 interview. Results Qualitative evidence identified barriers to reaching diagnosis, and limited interactions with primary care due to a lack of available treatments/interventions, stigma and disbelief in ME/CFS as a condition. In each year of interest, crude prevalence in the primary care setting ranged between 94.9/100,000 (95% CI: 91.5-98.5) and 103.9/100,000 population (95%CI: 100.3-107.7), equating to between 20,140 and 22,050 people living with ME/CFS in Australia in 2020. Higher rates were observed for age groups 50-59 years and 40-49 years. Rates were substantially higher in females (130.0-141.4/100,000) compared to males (50.9-57.5/100,000). In the context of the qualitative evidence, our prevalence rates likely represent an underestimate of the true prevalence of ME/CFS in the Australian primary care setting. Conclusion ME/CFS affects a substantial number of Australians. Whilst this study provides prevalence estimates for the Australian primary care setting, the qualitative evidence highlights the limitations of these. Future research should focus on using robust case ascertainment criteria in a community setting. Quantification of the burden of disease can be used to inform health policy and planning, for this understudied condition.